(untitled) (Journal of the College of Basic Education, 2024)
This study aimed to reveal the effectiveness of the computerized (KUD) strategy in the collection of the Arabic language subject among middle school students, in addition to identifying the teaching steps according to the (KUD) strategy. Effectiveness in the achievement of the Arabic language subject among middle school students?” The study started from the hypothesis that “there are statistically significant differences at the level of significance (0.05) between the average test scores of the students according to the (KUD) strategy and the usual method in the academic achievement test.” On the descriptive analytical approach as the appropriate approach for the study, and the study population consisted of middle school students at (Al-Durgham Secondary School for Boys) affiliated to Al-Karkh Second Education, and the study sample consisted of (43) students in the third intermediate stage, and the study reached several conclusions, the most important of which is the existence of significant differences Statistical significance at the level of significance (0.05) between the mean scores of the students’ test according to the (KUD) strategy and the usual method in the academic achievement test, and the difference is in favor of the (KUD) strategy. It turned out that the lowest score in the (KUD) strategy was (81), and in the usual method, the lowest score was obtained by the student (62). It also turned out that the highest score in the (KUD) strategy was (97), and in the usual method, the highest student got a score of (90).